2012
DOI: 10.1016/j.juro.2012.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Botulinum Neurotoxin A on Bladder Contractile Responses to Activation of Efferent Nerves, Smooth Muscles and Afferent Nerves in Rats

Abstract: The order of inhibitory potency of botulinum neurotoxin A was efferent nerve terminals >L-type voltage-gated Ca(2+) channels >afferent nerve terminals. Since the inhibitory effects on L-type voltage-gated Ca(2+) channels and efferent nerve terminals were observed at similar botulinum neurotoxin A concentrations, the inhibitory effect of botulinum neurotoxin A on L-type voltage-gated Ca(2+) channels may have an important role in regulating and stabilizing bladder activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
1
15
1
Order By: Relevance
“…An early paper showed that BTXA inhibited release of ATP as well as ACh from parasympathetic nerves in the rat bladder [455] and confirmed subsequently [410,654]. More recent studies have shown that BTX also inhibited ATP release from urothelium ( [133,329,368,626]; and see [177]).…”
Section: Botulinum Toxin and Atp Releasementioning
confidence: 82%
“…An early paper showed that BTXA inhibited release of ATP as well as ACh from parasympathetic nerves in the rat bladder [455] and confirmed subsequently [410,654]. More recent studies have shown that BTX also inhibited ATP release from urothelium ( [133,329,368,626]; and see [177]).…”
Section: Botulinum Toxin and Atp Releasementioning
confidence: 82%
“…Our study completed the model of Smith et al and Takahashi et al [6,8] by controlling the viability of the bladder strips during the runs. We proved that the inhibitory effect of BoNT-A can be measured in vitro at low concentrations.…”
Section: Discussionmentioning
confidence: 96%
“…Howles et al on the other hand could not reproduce these measurements in another in vitro model [7]. Takahashi et al demonstrated inhibitory effect of BoNT-A in vitro however it was at a much higher concentration (>10 nM) than is used in clinical practice (10 U/1 mL onabotulinumtoxinA = 0.001 nM) [8]. In this study, we further developed and validated an in vitro model to measure the bioactivity of BoNT-A in lower concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…In general drugs targeting membrane receptors have a relatively fast response (seconds to minutes), whereas drugs for intracellular targets ( e.g. , forskolin and other enzyme inhibitors 36 , botulinum toxin 37 ) require additional incubation time (30 min 3 hr). Additionally, tissue thickness may play a role.…”
Section: Discussionmentioning
confidence: 99%